2018
DOI: 10.1080/09500693.2018.1460772
|View full text |Cite
|
Sign up to set email alerts
|

Do individual differences in children’s curiosity relate to their inquiry-based learning?

Abstract: This study investigates how individual differences in 7-to 9-yearolds' curiosity relate to the inquiry-learning process and outcomes in environments differing in structure. The focus on curiosity as individual differences variable was motivated by the importance of curiosity in science education, and uncertainty being central to both the definition of curiosity and the inquiry-learning environment. Curiosity was assessed with the Underwater Exploration game (Jirout, J., & Klahr, D. (2012). Children's scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…In summary, focusing on the process of "figuring out" something children do not know, modeling and explicitly prompting exploration and question asking, and supporting metacognitive and creative thinking are all ways to promote curiosity and support effective cognitive engagement during learning. These methods are consistent with inquiry-based and active learning, which both are grounded in constructivism and information gaps similar to the current operationalization of curiosity (Jirout and Klahr, 2012;Saylor and Ganea, 2018;van Schijndel et al, 2018). Emphasizing performance, such as academic climates focused on teaching rote procedures and doing things the "correct" way to get the right answer, can suppress or discourage curiosity.…”
Section: Promoting Curiosity In Young Childrenmentioning
confidence: 71%
“…In summary, focusing on the process of "figuring out" something children do not know, modeling and explicitly prompting exploration and question asking, and supporting metacognitive and creative thinking are all ways to promote curiosity and support effective cognitive engagement during learning. These methods are consistent with inquiry-based and active learning, which both are grounded in constructivism and information gaps similar to the current operationalization of curiosity (Jirout and Klahr, 2012;Saylor and Ganea, 2018;van Schijndel et al, 2018). Emphasizing performance, such as academic climates focused on teaching rote procedures and doing things the "correct" way to get the right answer, can suppress or discourage curiosity.…”
Section: Promoting Curiosity In Young Childrenmentioning
confidence: 71%
“…The second answer is that researchers from both domains may learn from each other's methods. For instance, epistemic curiosity researchers sometimes use behavioral or neuroscientific measures (Jirout and Klahr 2012;Kang et al 2009;Lowry and Johnson 1981;van Schijndel et al 2018) approaches virtually unknown in the situational interest domain (Hidi and Renninger 2019). A third answer is that such attempt may help reduce the plethora of questionnaires in use in the field.…”
Section: Discussionmentioning
confidence: 99%
“…(1) frequency of use of a special information station containing books, pictures, and filmstrips and (2) frequency of attendance of an optional film screening. Jirout and Klahr (2012) andvan Schijndel et al (2018) found in either title or topic and (2) whether a measure of situational interest was reported in full detail. Initially, 398 articles were retrieved.…”
Section: Discussionmentioning
confidence: 99%
“…The key dimensions identified in the framework for curiosity include: focus of curiosity (with four factors of physical, perceptual, social, and epistemic), scope of curiosity (breadth vs. depth), cause of curiosity (diversive vs. specific or interest vs. deprivation), and consistency of curiosity across situational contexts (state vs. trait) [9]. Curiosity is positively linked to inquiry-based learning [10]. Questions are artifacts of curiosity.…”
Section: Introductionmentioning
confidence: 99%